2021
DOI: 10.1155/2021/5552614
|View full text |Cite
|
Sign up to set email alerts
|

GABPA Expression in Endometrial Carcinoma: A Prognostic Marker

Abstract: Background. GA-binding protein A (GABPA), a transcription factor, is broadly involved in physiological and pathological processes. Several studies have investigated the relationship between GABPA expression level and outcomes of various malignancies. However, the function and clinicopathological significance of GABPA in endometrial carcinoma (EC) remain obscure. Methods. The GABPA mRNA expression in EC tissues and adjacent nonneoplastic tissues in the TCGA database was involved in our study. The protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…GABPA is a transcription factor in the ETS family ( 45 ) that is involved in the nuclear control of mitochondrial function and the expression of cytochrome oxidase c ( 46 , 47 ). Recent studies have indicated that GABPA is downregulated in clear cell renal cell carcinoma ( 48 ), endometrial carcinoma ( 49 ) and gastric cancer ( 50 ), and that high GABPA expression is associated with a lower survival rate of patients. In follicular thyroid carcinoma (FTC), GABPA directly regulates the expression of DICER1 and was also downregulated in clinical FTC samples ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…GABPA is a transcription factor in the ETS family ( 45 ) that is involved in the nuclear control of mitochondrial function and the expression of cytochrome oxidase c ( 46 , 47 ). Recent studies have indicated that GABPA is downregulated in clear cell renal cell carcinoma ( 48 ), endometrial carcinoma ( 49 ) and gastric cancer ( 50 ), and that high GABPA expression is associated with a lower survival rate of patients. In follicular thyroid carcinoma (FTC), GABPA directly regulates the expression of DICER1 and was also downregulated in clinical FTC samples ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deeper mining of the database and multiple examinations of clinical cohort 1 patients, LCSCs, and in vitro heterogeneous tumor model mice led us to identify an additional upstream transcription factor GABPA of hsa_circ_0006677. It has been demonstrated that GABPA levels in uence prognostic overall survival and disease-free survival and can be used as an independent predictor of clinical prognosis in endometrial cancer [34]. GABPA directly regulates DICER1 in follicular thyroid cancer, which acts as a tumor suppressor and is shown to be downregulated in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, GABPA and TERT expression even anti-correlated with each other in these tumors, suggesting a more complicated in vivo relationship between them ( 59 ). Like other tumor suppressors, the aberrant promoter hypermethylation and/or copy number loss contribute to the downregulation of GABPA or GABPB1 in the cancer types above ( 56 , 59 61 ). Collectively, GABPA and GABPB1 functions are context- or cell type-dependent, and caution should be taken to target them for telomerase-based cancer therapy.…”
Section: The Activating Tert Promoter Mutation In Ucsmentioning
confidence: 99%
“…Indeed, following stable GABPB1 knockdown, glioblastoma cells carrying C228T or C250T TERT promoters undergo diminished TERT/telomerase expression, progressive telomere erosion and eventual loss of tumorigenic potential (55). However, GABPA and GABPB1 stimulate TERT transcription, but several lines of evidence suggest that they may serve as tumor suppressors in other cancer types regardless the presence or absence of TERT promoter mutations (56,(58)(59)(60)(61)(62)(63). In UCBs, TCs and renal cell carcinomas (RCCs), GABPA or GABPB1 inhibition promotes their stemness and invasiveness, despite downregulation of TERT expression (59, 60, 63).…”
Section: The Activating Tert Promoter Mutation In Ucsmentioning
confidence: 99%